2015
DOI: 10.1097/inf.0000000000000571
|View full text |Cite
|
Sign up to set email alerts
|

Review of Tenofovir Use in HIV-infected Children

Abstract: Tenofovir disoproxil fumarate (TDF) is approved by the Food and Drug Administration for use in children ages 2 years and older and is recommended by the World Health Organization for use as a preferred first-line nucleotide reverse transcriptase inhibitor in adults and adolescents ages 10 years and older. The simplicity of once daily dosing, few metabolic side effects and efficacy against hepatitis B virus make TDF suitable for use in a large scale program. Unlike thymidine analoge nucleoside reverse transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 74 publications
(80 reference statements)
1
23
0
Order By: Relevance
“…tenofovir (TDF) is unavailable for children aged <2 years, but in those aged >3 years, efforts should be made to harmonize with adult practices and to use emtricitabine (FDC)-containing regimens for children, including TDF + 3TC (as FDC) to be given with EFV (triple pediatric FDC) or NVP. TDF has been associated with favorable outcomes in pediatric salvage therapy studies [72], However, it has been associated with bone mineral density loss, increased bone turnover as well as changes in serum calcium, phosphate, parathyroid hormone, vitamin D level and urinary calcium excretion in children [73][74][75]. It is advised to avoid TDF in patients with baseline renal insufficiency.…”
Section: Malnutritionmentioning
confidence: 98%
See 1 more Smart Citation
“…tenofovir (TDF) is unavailable for children aged <2 years, but in those aged >3 years, efforts should be made to harmonize with adult practices and to use emtricitabine (FDC)-containing regimens for children, including TDF + 3TC (as FDC) to be given with EFV (triple pediatric FDC) or NVP. TDF has been associated with favorable outcomes in pediatric salvage therapy studies [72], However, it has been associated with bone mineral density loss, increased bone turnover as well as changes in serum calcium, phosphate, parathyroid hormone, vitamin D level and urinary calcium excretion in children [73][74][75]. It is advised to avoid TDF in patients with baseline renal insufficiency.…”
Section: Malnutritionmentioning
confidence: 98%
“…In adults, the Development of ARV Therapy in Africa trial showed small changes in glomerular filtration rates compared with other ARVs [76], although this may be because renal toxicities take a longer time to manifest. It is advised that children on TDF undergo monitoring of serum creatinine, urine glucose and urine protein approximately every 3-6 months [75]. The need for routine renal and bone density monitor may be an impediment to its routine use in resource-restricted settings and further data are needed in the pediatric setting.…”
Section: Malnutritionmentioning
confidence: 98%
“…Weight band dosing in children >3 years has been shown to have good short-term safety profile with equivalent pharmacokinetics [54]. However, there are concerns regarding long-term effects on bone mineral deposition and renal toxicity [55]. Tenofovir is currently being evaluated in adolescents >12 years of age in combination with elvitegravir and with other agents [56].…”
Section: Retention In Care and Antiretroviral Therapymentioning
confidence: 99%
“…The clinical implication of this remains unclear given the often short duration of many studies. Studies with a longer duration may be needed to evaluate clinically important complications [39].…”
Section: Discussionmentioning
confidence: 99%